2011
DOI: 10.1073/pnas.1116386108
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of β-catenin from mature hepatocytes of mice promotes expansion of hepatic progenitor cells and tumor development

Abstract: Depletion of β-catenin impairs regeneration of the rapid turn-over gut epithelial cells, but appears dispensable for that of the slow turn-over mature hepatocytes in mice until 1 y of age. As the life span of mature murine hepatocytes is about 400 d, we studied conditional β-catenin knockout mice (Alb-Cre;Ctnnb1 flx/flx ) until 20 mo of age to determine the function of β-catenin in the postnatal liver. β-catenin was absent from the hepatocytes of β-catenin knockout mice 4 wk after delivery. From 9 mo of age, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 31 publications
4
30
0
Order By: Relevance
“…1F). The recovery of Rpt2 at P40 in the livers of Rpt2 f/f ;Alb mice might be attributed to rapid hepatocytic death due to impairment of proteasome activity, followed by compensatory regeneration of hepatocytes from oval cells, which express low levels of albumin (40). Collectively, these data indicate that at P30, Rpt2 f/f ;Alb mice exhibit liver injury accompanied by reduced proteasome activity in the liver.…”
Section: Generation Of Mice With Decreased Proteasome Activity-tomentioning
confidence: 61%
“…1F). The recovery of Rpt2 at P40 in the livers of Rpt2 f/f ;Alb mice might be attributed to rapid hepatocytic death due to impairment of proteasome activity, followed by compensatory regeneration of hepatocytes from oval cells, which express low levels of albumin (40). Collectively, these data indicate that at P30, Rpt2 f/f ;Alb mice exhibit liver injury accompanied by reduced proteasome activity in the liver.…”
Section: Generation Of Mice With Decreased Proteasome Activity-tomentioning
confidence: 61%
“…This result opens a new theoretical option for increasing the endogenous regenerative capacity of the liver. The amplification of stem/progenitor cell pool carries increased risk of tumor formation [29][30][31][32][33][34][35], although there are contradictory results as well [36]. Our results show that the DEN-AAF/CCl 4 model is as efficient a carcinogenesis model as the original Solt-Farber model and that the AAF/CCl 4 treatment is a powerful tumor promoter.…”
mentioning
confidence: 53%
“…Thus, the increased number of stem cells does not indicate persistently higher tumor incidence. The recently revealed new results about the regulation of the stem cell compartment [31][32][33][34][35][36] may give us the tool to safely expand the pool of these cells in liver, which may result in clinically applicable increased regenerative capacity.…”
mentioning
confidence: 99%
“…In the cell migration assay, H1299 and MCF7 migrated cells were collected after 2h; data are the mean ± SEM of three separate experiments (D), * P < 0.05. relatively low, suggesting that USP14 might not be involved in liver cancer tumorigenesis -this may, in fact, hint toward the mechanism involved in USP14's effects on cancer. In a previous study, we found that β-catenin protein levels sharply decrease in conjunction with USP14 silencing in A549 cells [12], researchers have likewise found that β-catenin, a key member in the Wnt pathway that promotes proliferation in various tumors [33][34][35][36][37][38], is controlled through ubiquitination [39][40][41]. Given this information, SOX1, a developmental gene, may function as a tumor suppressor by interfering with Wnt/β-catenin signaling in the development of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%